Correction: Patchouli oil isolated from the leaves of Pogostemon cablin ameliorates ethanol-induced acute liver injury in rats via inhibition of oxidative stress and lipid accumulation. Issue 50 (14th August 2018) - Huang, Qiong-Hui; Wu, Xue; Chen, Xiao-Hong; Wu, Jia-Zhen; Su, Zi-Ren; Liang, Jia-Li; Li, Yu-Cui; Lai, Xiao-Ping; Chen, Jian-Nan; Liu, Yu-Hong
Abstract : Correction for 'Patchouli oil isolated from the leaves of Pogostemon cablin ameliorates ethanol-induced acute liver injury in rats via inhibition of oxidative stress and lipid accumulation' by Qiong-Hui Huang et al., RSC Adv., 2018, 8, 24399–24410.